2012
DOI: 10.4025/actascibiolsci.v34i4.8535
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme expression in indica and japonica rice cultivars under saline stress

Abstract: ABSTRACT. The southern State of Rio Grande do Sul (RS) is the main rice producer in Brazil with a 60% participation of the national production and 86% participation of the region. Rice culture irrigation system is done by flooding, which leads to soil salinization, a major environmental constraint to production since it alters the plants' metabolism exposed to this type of stress. The indica cultivar, widely used in RS, has a higher sensitivity to salinity when compared to that of the japonica cultivar in othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…It is estimated that 50% of world rice production affected more or less by drought (Bouman et al 2005). As previously reported, the yield loss due to cold stress is up to 80% in Japan (Shimono et al 2007), 26% in Korea (Lee 2001), 25% in Brazil (1997Lima et al 2012;Cruz et al 2013), while in 2001, the Australian rice industry suffered an average loss of Aus $23.2 million per year from cold damage (Farrell et al 2001). It has been repeatedly found that certain biochemicals, known as effectors/elicitors, applied to plants in low concentrations can activate biochemical, genetic and physical defence mechanisms (Garcia-Brugger et al 2006).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is estimated that 50% of world rice production affected more or less by drought (Bouman et al 2005). As previously reported, the yield loss due to cold stress is up to 80% in Japan (Shimono et al 2007), 26% in Korea (Lee 2001), 25% in Brazil (1997Lima et al 2012;Cruz et al 2013), while in 2001, the Australian rice industry suffered an average loss of Aus $23.2 million per year from cold damage (Farrell et al 2001). It has been repeatedly found that certain biochemicals, known as effectors/elicitors, applied to plants in low concentrations can activate biochemical, genetic and physical defence mechanisms (Garcia-Brugger et al 2006).…”
Section: Introductionmentioning
confidence: 95%
“…), 26% in Korea (Lee ), 25% in Brazil (1997, 2011, 2012; Lima et al . ; Cruz et al . ), while in 2001, the Australian rice industry suffered an average loss of Aus $23.2 million per year from cold damage (Farrell et al .…”
Section: Introductionmentioning
confidence: 98%
“…Cold tolerance is one of the major qualities, a rice cultivar is expected to have since the low temperatures have caused significant yield losses in many parts of the world [1]. Low temperatures during the flowering stage cause incomplete panicle exertion, spikelet sterility, and Original Research Article degeneration of the spikelet resulting in low grain formation [2].…”
Section: Introductionmentioning
confidence: 99%
“…In this region, as well as in Uruguay and Argentina, indica rice accounts for almost the totality of cultivated rice. Low temperature can reduce up to 25% of the final yield (Bierlen et al 1997;Clayton and Neves 2011;Lima et al 2012).…”
Section: Introductionmentioning
confidence: 99%